Neuropsychiatric genetics in developing countries: Current challenges (2014)
Neuropsychiatric disorders (NPDs) constitute a heavy burden on public health systems around the world and studies have demonstrated that the negative impact of NPDs is larger in Low and Middle Income Countries (LMICs). In recent decades, several studies have come to the understanding that genetic factors play a major role in the risk for a large number of NPDs. However, few neuropsychiatric genetics studies have been published from LMICs. In this Editorial, we discuss important issues impinging on advances in neuropsychiatric genetics research in LMICs. It is essential that scientists educate policymakers and officials of funding agencies on the importance of providing adequate funding for research in these areas. Development of local well-supported research programs focused on NPD genetics should be an important asset to develop; it would facilitate the establishment of sustainable research efforts that could lead to appropriate diagnosis and specific, affordable and feasible interventions in LMICs. It is important to point out that research into the biological basis of human NPDs is not only an academic effort reserved for a few elite institutions in economically developed countries, but it is vitally important for the mental health of people around the world.